Influence of different irrigation intervals on growth and physical characteristics of peach (Prunus persica) - KOUR, GAGANPREET; WALI, V K; BAKSHI, PARSHANT; JASROTIA, AMIT; KHUSHU, M K (The Indian Journal of Agricultural Sciences, 2026)
The aim of this experiment was to determine the effect of different irrigation water application levels on growth of three peach (Prunus persica L.) cultivars, viz. Florida Prince, Shan-e-Punjab and Early Grande irrigated by basin irrigation.Evapotranspiration and vegetative growth parameters (plant height and volume), physical characteristics(fruit length, fruit diameter, fruit weight, specific gravity, stone weight and pulp weight)of 3-4 year old peach plants were recorded during both the seasons. The plants were subjected to four different irrigation treatments based on evapotranspiration (Et)of 20 mm, 30 mm, 40 mm, 50 mm and rainfed. The maximum plant height (2.74 m and 3.48 m), plant volume (11.34 m3 and 17.08 m3), fruit length (4.98 cm and 5.67 cm), fruit diameter (4.31cm and 5.10 cm), fruit weight (85.69 g and 96.11g), specific gravity (0.99 and 1.03), stone weight (4.77g and 5.56g) and pulp weight (80.30g and 91.65g) were recorded at I40 (40 mm Et) levels based irrigation levels during 2010 and 2011.